Perkembangan Dana Pihak Ketiga dan Pembiayaan pada Bank Syariah di Masa Pandemi Covid-19 - Kirana, Diajeng Ayunda Candra (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
The research was conducted with the aim of analyzing and interpreting the role of Third-Party Funds (DPK) and Disbursed Financing (PYD) on the development of Islamic banking during the Covid-19 pandemic. The research method used is the descriptive qualitative method and data collection was carried out using library research techniques, namely by collecting data from books, journals, theses, and other supporting articles related to the topic of discussion in this study. The data is processed by analyzing various facts and then explained in more detail and easily understood by the reader. The results of this research are the development of Islamic banking is determined from the increase in total assets, Third Party Funds and Disbursed Financing which based on the results of the analysis from year to year has increased although not significantly. Islamic banking has become a stable Islamic financial institution during the pandemic. The highest total assets are in Islamic Commercial Banks. Third-Party Funds during this pandemic are still stable. And in terms of disbursed financing or credit, the highest use is in consumption. DPK and PYD are among the factors that determine the development of Islamic banking in Indonesia, especially during the Covid-19 pandemic.